2017
DOI: 10.1038/ncomms15467
|View full text |Cite
|
Sign up to set email alerts
|

Probing intermediates of the induction period prior to nucleation and growth of semiconductor quantum dots

Abstract: Little is known about the induction period before the nucleation and growth of colloidal semiconductor quantum dots. Here, we introduce an approach that allows us to probe intermediates present in the induction period. We show that this induction period itself exhibits distinct stages with the evolution of the intermediates, first without and then with the formation of covalent bonds between metal cations and chalcogenide anions. The intermediates are optically invisible in toluene, while the covalent-bonded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
299
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(327 citation statements)
references
References 80 publications
(216 reference statements)
22
299
5
1
Order By: Relevance
“…The relation between CdS MSC−311 and RQDs in the current study is similar to that proposed for CdTe MSC−371 and RQDs. 46 We also explored the formation of IP311 with MALDI-TOF MS, as shown in Figure S5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between CdS MSC−311 and RQDs in the current study is similar to that proposed for CdTe MSC−371 and RQDs. 46 We also explored the formation of IP311 with MALDI-TOF MS, as shown in Figure S5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…31 The definition of monomers (such as Cd 1 S 1 or Cd 2 S 2 ) can be found elsewhere. 40−45 Very recently, 46 a study was conducted on the induction period prior to nucleation and growth of cadmium telluride (CdTe) RQDs. This study suggested that CdTe MSC precursors were formed in the induction period.…”
mentioning
confidence: 99%
“…Manipulating functional materials at atom-by-atom basis represents the most ambitious dream of scientists in nanochemistry 1 6 . Such dream should be rooted in precise understanding on growth mechanism of nanoparticles (NPs) at atomic level, which has puzzled nanoscience research community for decades, but little has been unraveled so far 7 , 8 . Fundamental breakthrough on particle growth mechanism may come with the recently discovered molecular-like metal NPs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pathway from the early phase separation of atoms, ions, or molecules from solutions to the nanoparticle formation is still unclear . Toward filling this gap, multiple‐step models have been recently proposed, which emphasize the presences of several intermediate states prior to nucleation, such as amorphous precursors,[5c,6] magic‐size clusters, condensed liquid phase, prenucleation clusters, etc. Although it is suggested that the energetic barrier for multistep nucleation via intermediate states is lower than that expected in a classical nucleation picture, debates remain due to the lack of direct experimental evidence for early crystallization.…”
mentioning
confidence: 99%
“…Although it is suggested that the energetic barrier for multistep nucleation via intermediate states is lower than that expected in a classical nucleation picture, debates remain due to the lack of direct experimental evidence for early crystallization. [4b,5a,c,7,11]…”
mentioning
confidence: 99%